Development of a Geographic Information System Quality Evaluation Framework Using WebQual 4.0 and ISO/IEC 25010 Approaches: A Case Study on Bali Province Balisatudata Website (Decode: Jurnal Pendidikan Teknologi Informasi, 2025)
Geographic Information Systems (GIS) are important tools for managing spatial data in various sectors such as urban planning and environmental management. However, poor GIS quality can hinder accurate decision-making. This study aims to develop an integrated GIS quality evaluation framework by combining two approaches: WebQual 4.0 and ISO 25010. WebQual 4.0 focuses on quality from the user's perspective, while ISO 25010 evaluates the technical characteristics of the software.This research was conducted to evaluate the impact of comparing measurement results using the WebQual 4.0 and ISO 25010 methods on GIS quality, as well as to develop an integrated framework that includes practical recommendations for evaluating GIS quality using the WebQual 4.0 and ISO 25010 methods. Data was collected from 100 active GIS users on the balisatudata.baliprov.go.id website and analyzed using the Importance Performance Analysis (IPA) method. The results showed that the integration of the two methods produced a more comprehensive evaluation of GIS quality compared to a single method. Key findings include quality attributes that need improvement, such as classification accuracy and data position accuracy, as well as system accessibility and reliability. This framework provides an important contribution as a guideline for GIS developers in improving system quality from technical, data, and user satisfaction aspects, as well as a basis for data-driven decision-making.